(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
In this era of educational technology, the English language is more than ever the world language, and the speaking skill is considered the most important skill that students need to master, because its main goal is communication. However, to acquire this skill is not easy, and may present difficulties, especially for students of English as a second language. Teaching this skill plays then an essential role, and modern techniques and methods are prevailed. The use of technology and multimedia resources come to replace traditional methods to grab students’ attention, increase their motivation in the classroom and to succeed in classroom goals. The elaboration of a multimedia resources guide is proposed to assist teachers and help students improve their speaking skill